Clinical and serological characterization of acute pleuropericarditis suggests an autoinflammatory pathogenesis and highlights risk factors for recurrent attacks - Kaudewitz, Dorothee; John, Lukas; Meis, Jan; Frey, Norbert; Lorenz, Hanns-Martin; Leuschner, Florian; Blank, Norbert (Clinical research in cardiology, 2024)
Purpose  We describe the manifestations and course of patients with pleuropericarditis (PP). Serum parameters were analyzed to evaluate the contribution of autoimmune and autoinflammatory mechanisms to PP pathogenesis. Finally, we outline risk factors for recurrent PP attacks. - Methods  Electronic medical records of the University Hospital Heidelberg were screened for PP diagnosis between the years 2009 and 2021. A total of 164 patients were detected and compared to patients suffering from systemic lupus erythematosus (SLE)-associated PP. Follow-up data were collected until January 2023. - Results  In 57.3% of a total of 164 PP cases, no trigger was identified (idiopathic PP). The clinical manifestations were similar in subgroups with different triggers (idiopathic, post-cardiac injury and post-infectious). None of the patients in the idiopathic-PP (i-PP) group fulfilled the diagnostic criteria of an autoimmune disease and the i-PP group could be clearly discriminated by clinical, epidemiological and serological means from the control cohort of SLE-associated PP. After a median follow-up of 1048 days, the majority of PP patients (72.7%) had at least one PP relapse. Univariate analyses showed that CRP, SAA (serum amyloid A), troponin T, NT-BNP and post-cardiac injury were negatively correlated, while the presence of fever and an idiopathic trigger were positively correlated with recurrence of PP. Multivariate analyses showed that fever, an idiopathic trigger and low SAA values were risk factors for PP recurrence. - Conclusion  This study highlights that most cases of PP are idiopathic and PP cases with various triggers have an identical clinical phenotype. Our data suggest that the clinical, epidemiological and serological characteristics of idiopathic PP considerably differ from patients with PP caused by autoimmune disease like SLE. We further demonstrate that PP has a high risk of recurrence and identify factors associated with this risk, allowing for a targeted secondary prophylaxis.